Carbon management systems and environmental performance: the role of technological capability as a mediator - Nazaria Md.Aris,; Sofiah Md Auzair, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Manufacturing firms are increasingly pressured to mitigate carbon emissions resulting from their operations, mainly due to stakeholders’ negative reactions to environmental pollution. However, inadequate carbon management and technological capability can impede firms' environmental performance, producing a competitive disadvantage. Therefore, this study adopts the Natural Resource-Based View to investigate the effect of carbon management systems on the environmental performance of Malaysian manufacturing firms, specifically via the mediating role of technological capability. To meet the research objectives, a survey was conducted among 115 manufacturing firms registered under the Federation of Malaysian Manufacturers. Data analysis using structural equation modelling revealed significant positive relationships between carbon management systems, technological capability, and environmental performance, with technological capability mediating the effect of carbon management systems on environmental performance. Industry players and policymakers can leverage these insights to enhance manufacturing firms’ carbon management strategies and subsequently, attain the environmental performance levels necessary to achieve net zero emissions.